Barriers and enablers of type 2 diabetes self‐management in people with severe mental illness. (17th March 2017) - Mulligan, Kathleen; McBain, Hayley; Lamontagne‐Godwin, Frederique; Chapman, Jacqui; Haddad, Mark; Jones, Julia; Flood, Chris; Thomas, David; Simpson, Alan
Abstract: Background: People with diabetes and severe mental illness (SMI) experience poorer outcomes than those with diabetes alone. To improve outcomes, it is necessary to understand the difficulties that people with SMI experience in managing their diabetes. Aims: To identify barriers and enablers to effective diabetes self‐management experienced by people with SMI and type 2 diabetes. Method: Qualitative methodology using semi‐structured interviews was employed. Development of the interview topic guide and analysis of the transcripts were informed by the Theoretical Domains Framework for behaviour change, which consists of fourteen theoretical domains that have been found to influence behaviour. Results: Fourteen people with SMI and type 2 diabetes took part in the study. Participants considered diabetes self‐management to be important, were aware of the risks of poor diabetes control but struggled to follow recommended advice, particularly if their mental health was poor. Support from family and health professionals was considered an important enabler of diabetes self‐management. Conclusions: New approaches are required to support diabetes self‐management in people with SMI. This study identified some of the important domains that may be targeted in new interventions.